Preliminary study on termites in oil palm plantation / Mohd Shyawal Amran - Amran, Mohd Shyawal (Faculty of Plantation and Agrotechnology, 2015)
Malaysia is one of the leading producers and exporters of palm oil in the world with 4.69 mil hectares plan ted with oil palm (MPOB). Suitable land for oil palm planting is rapidly diminishing and moving into peat area is inevitable. A peat area with a lot of woody material is a natural habitat of the subterranean termite. Termite is one of the common pests of oil palm planted on peat in Malaysia and Indonesia. Through this study, we can identify how much the volume of damage rate done by termites in oil palm plantation. Termite generally attack the palm from the spear in immature palm due to the energy requirement and level of water table. After that, this study evaluates the population size of termites in oil palm. The increasing of termite population in certain area of oil palm give effect to the performance growth of tree and also yield. Besides that, we also analyzed what is the significant abiotic factor influenced the termite become more active such as rainfall which is important to maintain the activities of termites. However, the present of warm, humid and moist environment around agriculture area create a consistently conducive environment where termites can remain active throughout the year. Plantation management must be vigilant in identifying the earliest symptoms of termite infestation where curative measured may still save the palm. Inspection of the source of termite in an infested area such as the drainage area and wood stump are really important. Sanitation activity indirectly reduced the chances of termite for breeding and nesting.